THE EFFECT OF SOCIAL SECURITY ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLES (Study from Administrative Section of Texas Public Health Facilities) - Jorge O Brusa; Mohsen Bahmani-Oskooe (PT. Radja Intercontinental Publishing, 2020)
This study aims to determine“The Effect of Social Security on Employee Performance with Job Satisfaction as an Intervening Variable (Case Study in the Administrative Section of PT. Auto Padu Kuala Tanjung Batubara)”. The results of this study indicate that 1) it can be seen that tcount (7.314) > ttable (1.685), likewise with a significance value of 0.00 <0.05 it can be concluded that the first hypothesis is accepted, meaning that the social security variable(X) positive and significant effecton job satisfaction (Y1). 2) it can be seen that tcount (2.593) > ttable (1.685), and a significance value of 0.01 <0.05, it can be concluded that the second hypothesis is accepted, meaning social security(X) positive and significant effecton employee performance (Y2). 3) it can be seen that tcount (5.131) > ttable (1.685), and the significance value is 0.00 <0.05, it can be concluded that the third hypothesis is accepted, meaning job satisfaction (Y1)positive and significant effecton employee performance (Y2). 4) the direct effect of variable X on variable Y2 is 0.313. While the indirect effect through the Y1 variable is 0.765 x 0.619 = 0.473, the calculation results obtained show that the indirect effect through the Y1 variable is greater than the direct effect on the Y2 variable.